2011
DOI: 10.1007/s11243-011-9480-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mono- and dinuclear copper(I) complexes with 3-(2-pyrimidinyl)-1,2,4-triazine

Abstract: The mono-and dinuclear Cu(I) complexes [CuI(PPh 3 )(pmtz)] (1) and [{Cu(PPh 3 ) 2 } 2 (l-pmtz)](ClO 4 ) 2 (2), where pmtz is 3-(2-pyrimidinyl)-1,2,4-triazine, have been synthesized and characterized. Single-crystal X-ray diffraction analysis reveals that the pmtz acts as a bidentate ligand in complex 1, whereas in complex 2 the pmtz coordinates as a bis-bidentate chelate, assembling two identical {Cu(PPh 3 ) 2 } moieties into a copper(I) dimer with a triple-decker sandwich structure involving phenyl/pmtz/ phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…However, in this case, the highest shift should be observed for complex (3) due to an electron-withdrawing chloride substituent in the 2-Me-5-ClquinCOO ligand but it is not. 2.2548 (7) 2.2268(9) 2.2447(9) Angles N(1)-Cu(1)-O (1) 80.01 (7) 79.78 (8) 79.64(9) N(1)-Cu(1)-P (1) 117.48 (6) 107.05 (6) 110.97(7) O(1)-Cu(1)-P (1) 103.65 (5) 111.64 (6) 109.88(8) N(1)-Cu(1)-P (2) 109.80 (6) 123.20 (6) 119.38(8) O(1)-Cu(1)-P (2) 105.70 (5) 112.17 (6) 102.47(7) P(1)-Cu(1)-P (2) 127.53 (3) 117.14(3) 123.75(3) Symmetry transformations used to generate equivalent atoms: 1 1 þx,y,z; 2 x,y, À 1þ z. Fig.…”
Section: Absorption and Emission Electronic Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, the highest shift should be observed for complex (3) due to an electron-withdrawing chloride substituent in the 2-Me-5-ClquinCOO ligand but it is not. 2.2548 (7) 2.2268(9) 2.2447(9) Angles N(1)-Cu(1)-O (1) 80.01 (7) 79.78 (8) 79.64(9) N(1)-Cu(1)-P (1) 117.48 (6) 107.05 (6) 110.97(7) O(1)-Cu(1)-P (1) 103.65 (5) 111.64 (6) 109.88(8) N(1)-Cu(1)-P (2) 109.80 (6) 123.20 (6) 119.38(8) O(1)-Cu(1)-P (2) 105.70 (5) 112.17 (6) 102.47(7) P(1)-Cu(1)-P (2) 127.53 (3) 117.14(3) 123.75(3) Symmetry transformations used to generate equivalent atoms: 1 1 þx,y,z; 2 x,y, À 1þ z. Fig.…”
Section: Absorption and Emission Electronic Spectramentioning
confidence: 99%
“…Among the most studied emissive complexes are these with N-heterocyclic chelating ligands. In the case of Cu(I) complexes the ligands are very important because the ligands can modulate the emissive properties from the metal-toligand charge-transfer (MLCT) excited state [4][5][6][7][8]. Moreover the phosphine auxiliary ligands occurred in these complexes play a positive role in stabilizing the Cu(I) center, although they are not involved in the MLCT transition, and exert important effects on the photophysical properties of Cu(I) complexes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In Cu(I) systems, selection of the appropriate N-heterocyclic chelating ligand is the key, because it can modulate the emissive properties from the metal-to-ligand charge-transfer (MLCT) excited state [4][5][6][7][8]. In addition, the phosphine auxiliary ligands play a positive role in stabilizing the Cu(I) center, albeit they are not involved in the MLCT transitions, and also exert important effects on the photophysical properties of their Cu(I) complexes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have initiated the investigation of photoactive monoand binuclear copper(I) complexes featuring multi-site N-heterocyclic chelating ligands [16][17][18][19][20]. It is shown that both N-heterocyclic chelate and the ancillary ligand such as halide and phosphine have a significant impact on the formation and photophysical properties of the corresponding Cu(I) species.…”
mentioning
confidence: 99%
“…Further support is given by a close matching of the absorption spectra in the high-energy region (≤350 nm) of Hbmp and its halide complexes 1-3. In addition to the high-energy absorptions, complexes 1-3 have a comparatively weak low-energy absorption tail (ε b 1000 M − 1 cm − 1 ) which somewhat varies with the halide ligand, assigned to a metal-toligand charge-transfer (MLCT) transition from the d π orbital of the (3d 10 )Cu center to the unoccupied π* orbital of the Hbmp ligand, probably mixed with some halide-to-ligand charge-transfer (XLCT) character [6,9,[13][14][15][16][17][18]29].…”
mentioning
confidence: 99%